THE ROLE OF THE FAMILY IN FIGHTING DESTRUCTIVE IDEAS - Khaydarov Okhinjon Murodjonovich (Bright Mind Publishing, 2025)
The article highlights the role of the family in the fight against destructive ideas in the upbringing of children.
Keywords: Child, spoiler, idea, family, upbringing, tradition, customs, values.